please solve this as fast as possible
Attachments:
![](https://hi-static.z-dn.net/files/d11/b021ccedb90c91c8792ecee97fdebb0d.jpg)
Answers
Answered by
2
Answer:
see step by step.....
Step-by-step explanation:
∫
sin
2
x.cos
2
x
sin
6
x+cos
6
x
dx
first resolve , sin^6x + cos^6x
= (sin²x)³ + (cos²x)³
= (sin²x + cos²x)(sin⁴x + cos⁴x - sin²x.cos²x)
=(sin²x + cos²x) {(sin²x + cos²x)² - 3sin²x.cos²x}
but we know, sin²x + cos²x = 1
so, sin^6x + cos^6x = (1 - 3sin²x.cos²x)
or, you can write cos^6x + cos^6x = sin²x + cos²x - 3sin²x.cos²x [ as we know, sin²x + cos²x = 1 ]
now, \int{\frac{(sin^2x+cos^2x-3sin^2x.cos^2x)}{sin^2x.cos^2x}}\,dx∫
sin
2
x.cos
2
x
(sin
2
x+cos
2
x−3sin
2
x.cos
2
x)
dx
= \int{sec^2x+cosec^2x-3}\,dx∫sec
2
x+cosec
2
x−3dx
= \int{sec^2x}\,dx-\int{cosec^2x}\,dx-\int{3}\,dx∫sec
2
xdx−∫cosec
2
xdx−∫3dx
= tanx - cotx - 3x + C
hence, \int{\frac{sin^6x+cos^6x}{sin^2x.cos^2x}}\,dx∫
sin
2
x.cos
2
x
sin
6
x+cos
6
x
dx
= tanx - cotx - 3x + C
Similar questions